STUDI KOMPARATIF INVESTASI EMAS DAN INVESTASI SAHAM PADA PT. ANEKA TAMBANG, TBK: ANALISA KINERJA KEUANGAN DAN PERSEPSI GENERASI Z - Dea Destari; Lily Rahmawati Harahap; Rahmi Aryanti; Sri Ermeila (Taksasila Edukasi Insani, 2026)
This study aims to analyze the comparison between the performance of gold investment and stock investment in PT. Aneka Tambang, Tbk, as well as to identify the perspectives of Generation Z investors in Palembang City toward both investment instruments. This research employed a mixed method approach using quantitative and qualitative methods. Quantitative data consisted of historical gold prices and stock prices of PT. Aneka Tambang, Tbk, which were analyzed through return calculations, risk measurement, and comparative statistical tests. Qualitative data were obtained through questionnaires distributed to 100 Generation Z respondents in Palembang City who were interested in gold and stock investments. Data analysis was conducted using the independent sample t-test. The results showed that there was no significant difference in the rate of return between gold investment and stock investment. However, there was a significant difference in the level of risk, where gold investment had a lower level of risk compared to stock investment. Furthermore, this study revealed that Generation Z in Palembang City showed greater interest in gold investment because it is considered safer and more stable than stock investment.Keywords : Investment, Gold, Stock, Return, Risk, Generation Z